If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 9 = -89 + -8x Reorder the terms: 9 + x = -89 + -8x Solving 9 + x = -89 + -8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8x' to each side of the equation. 9 + x + 8x = -89 + -8x + 8x Combine like terms: x + 8x = 9x 9 + 9x = -89 + -8x + 8x Combine like terms: -8x + 8x = 0 9 + 9x = -89 + 0 9 + 9x = -89 Add '-9' to each side of the equation. 9 + -9 + 9x = -89 + -9 Combine like terms: 9 + -9 = 0 0 + 9x = -89 + -9 9x = -89 + -9 Combine like terms: -89 + -9 = -98 9x = -98 Divide each side by '9'. x = -10.88888889 Simplifying x = -10.88888889
| 7x-(4-3x)=5+(3x-1) | | 5+3(2x+2)=6+4(x+1) | | 15=6x^2-23x-15 | | 3+4x+8x=15 | | (2x+3)+(x-7)=5x-(3x-7) | | (2x-2)+3x=128 | | (2x-2)+3x=2 | | 2x+123=5 | | (2x+4)(3x)=180 | | 2a(4a+3)= | | 7(m+9)=12+19m | | 64-32x+5x=-8+6+9x | | 4x+22=14x-78 | | 7/4x=400 | | 35x^2-100x-15=0 | | 1/3x+3/9a=40 | | 2x+5=43 | | 138-2x=34x+22 | | (4-2x)(1-3x)=6(x+1)(x-1) | | 4.5(x+1.5(x-6))=0 | | 12-9x=27-16x | | (4-x)(4+x)+2x=1-(x-5)(x+5) | | c=2/x^2 | | 5(x+3y)=20 | | 4x+7y=29 | | 7744=88 | | 887744=88 | | (2x+22)(3x)=180 | | -4x*-6=4 | | 3m=4m-5 | | 15(3x-1)-2(7x+2)= | | x^4+6x^2-27x=0 |